Role of organizational justice, organizational commitment and job satisfaction on quality of work life: case study of Pour-Sina state hospital personnel in Rasht - Alireza Hatam; Sajad Rezaei; Leila Kouchaki Nejad; Shahrokh Yousefzadeh (Tehran University of Medical Sciences, 2015)
Background ; Aim:‌ Improving the quality of work life in hospital personnel is introduced as one of the important factors for ensuring the sustainability of the health system. The aim of this study was to investigate the relationship among organizational justice and commitment, and job satisfaction with quality of work life in Pour-Sina state hospital personnel.  Materials ; Methods: ‌The study design was descriptive and cross-sectional, and statistical population included all of physicians, nurses, radiology and administrative staff and service workers of Poursina State Hospital in Rasht. 216 individuals were selected by quota sampling and filled the questionnaires on demographic information, quality of work life, organizational justice and commitment and job Descriptive Index‌(JDI).All data were analyzed with SPSS 16 software and by correlation coefficient and multiple regression. Results:‌ Among the demographic characteristics, only work history had a significant negative correlation with quality of work life ‌(r=-0.155,‌P<0.05).‌ All dimensions of organizational commitment‌(except continues commitment) and organizational justice had a positive and significant relationship with quality of work life(P<0.0001).in regression analysis variables of distributive justice (P=0.0001,β=0.318),pay satisfaction (P=0001.0,β=0.288), affective commitment (P=0.007,β=0.144), promotion satisfaction (P=0.003,β=0.172), procedural justice (P=0.013,β=0.139 ), and normative commitment (P=0.003, β=0.172) significantly predicted the levels of  quality of work life and totally explained 60% of shared variance‌‌(P<0.0001,F=46.913). Conclusion: individuals working in hospital are always at risk of burnout. Thus, it is proposed that much attention be paid to dimensions of job satisfaction, organizational commitment and justice in order to increase the quality of work life in hospital environments.